Argumentação, metáfora, textualidade e enunciação (Argumentation, métaphore, textualité et enonciation) - Silva, Soeli Maria Schreiber da (2015)
I study the metaphor in the poetry "Heart of a poet" by Paulo Leminski, recited by the author in the film "Life and Blood of Polish".I adopt the hypothesis of Eduardo Guimarães's metaphor (2011).I analyze the textuality in the integrative relation and the argumentative orientation of the metaphor in the concomitance of enunciators.KEYWORDS: Argumentation.Metaphor.Textuality.Enunciation.Determination.